PENGARUH PROGRAM UPAYA KHUSUS TERHADAP PRODUKTIVITAS, BIAYA POKOK DAN PENDAPATAN USAHATANI JAGUNG DI KABUPATEN LAMPUNG SELATAN - Syarinia Febriantika Agung; Agus Hudoyo; Achdiansyah Soelaiman (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
In 2014 corn production in Indonesia has not been able to meet its needs. Therefore, since 2015, the Government of Indonesia has launched a Special Effort Program (Upsus) to increase corn production through increasing its productivity and planting area. This study aims to determine the effects of Upsus program on productivity, standard costs, and income of corn farming in South Lampung Regency. The model used is multiple regression with productivity, standard cost, and income as the dependent variables, and Upsus and other control variables in the form of dummy variables as the independent variables. Data are the corn farming data in the rainy season (MH) and dry season (MK) during non-Upsus (2013/2014) and Upsus (2017/2018). The data were obtained from interviews with 32 respondents of corn farmers in Ketapang and Tanjung Bintang Districts. The results showed that the Upsus program had a statistically significant effects on increasing productivity, decreasing standard cost, and increasing corn farm income with 1% of the significance level.  Its productivity increased from 4.89 tons / ha to 5.37 tons / ha or an increase of  9.81%. Its standard cost decreased from IDR1,282/kg to IDR1,016/kg or a decrease of 20.67%. Its income increased from IDR 6.11 million/ha to IDR 8.39million /ha or an increase of 37.22%.Key words: income, productivity, standard cost, Upsus